Answer:
3x +13y = 14
6x +11y = -2
Explanation:
Substitute the given values into the equations and see which equations are satisfied.
• first set:
3(-4) +13(2) = -12 +26 = 14 . . . . true
6(-4) +11(2) = -24 +22 = -2 . . . . true
You have the answer at this point, but you can check the other choices if you wish.
___
• second set:
4(-4) +5(2) = -16 +10 = -6 ≠ 12 . . . . second set of equations is not the answer
___
• third set:
5(-4) +4(2) = -20 +8 = -12 ≠ 12 . . . . third set of equations is not the answer
___
• fourth set:
10(-4) +3(2) = -40 +6 = -34 ≠ 8 . . . . fourth set of equations is not the answer